2001
DOI: 10.1074/jbc.m103971200
|View full text |Cite
|
Sign up to set email alerts
|

C Terminus-mediated Control of Voltage and cAMP Gating of Hyperpolarization-activated Cyclic Nucleotide-gated Channels

Abstract: The hyperpolarization-activated cyclic nucleotidegated (HCN) family of "pacemaker" channels includes 4 isoforms, the kinetics and cAMP-induced modulation of which differ quantitatively. Because HCN isoforms are highly homologous in the central region, but diverge more substantially in the N and C termini, we asked whether these latter regions could contribute to the determination of channel properties. To this aim, we analyzed activation/deactivation kinetics and the response to cAMP of heterologously expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
2
52
1
Order By: Relevance
“…Of the four HCN isoforms known, HCN1 is the least sensitive to cAMP, and shifts of the channel activation curve caused by saturating cAMP concentrations are of the order of only a few mV (4,11,32,41). Because we found that only HCN1 binds filamin A, this appears to contrast with the hypothesis that interaction with filamin A serves the purpose of concentrating elements of the cAMP second messenger cascade in restricted locations for improved channel cAMP-dependent modulation.…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…Of the four HCN isoforms known, HCN1 is the least sensitive to cAMP, and shifts of the channel activation curve caused by saturating cAMP concentrations are of the order of only a few mV (4,11,32,41). Because we found that only HCN1 binds filamin A, this appears to contrast with the hypothesis that interaction with filamin A serves the purpose of concentrating elements of the cAMP second messenger cascade in restricted locations for improved channel cAMP-dependent modulation.…”
Section: Resultscontrasting
confidence: 54%
“…Heterologous expression of individual HCN isoforms does not normally result in currents whose properties reproduce entirely those of the native pacemaker (I f /I h ) currents (4,32). Part of this difference may be attributable to the existence of a "context" dependence of channel properties, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural analysis of HCN channels Shin et al, 2001;Viscomi et al, 2001;Wainger et al, 2001;Wang et al, 2001) points to the involvement of the COOH terminus and the S6 segments as physical domains involved in channel gating. Thus, trapping of the drug could be associated with physical occlusion of a large intracellular channel vestibule by the interaction between these and possibly other channel domains.…”
Section: Ivabradine Blocks Open F-channels Leading To Use-dependent mentioning
confidence: 99%